Markers of Angiogenesis Associated with Surgical Attenuation of Congenital Portosystemic Shunts in Dogs - Tivers, M.S. (J Vet Intern Med, 2014)
BACKGROUND: Dogs with congenital portosystemic shunts (CPSS) have hypoplasia of the intrahepatic portal veins. Surgical CPSS attenuation results in the development of the intrahepatic portal vasculature, the precise mechanism for which is unknown, although new vessel formation by angiogenesis is suspected. HYPOTHESIS: That the degree of portal vascular development and the increase in portal vascularization after CPSS attenuation is significantly associated with hepatic vascular endothelial growth factor (VEGF) and VEGF receptor 2 (VEGFR2) gene expression and serum VEGF concentration. ANIMALS: Client‐owned dogs with CPSS undergoing surgical treatment. Forty‐nine dogs were included in the gene expression data and 35 in the serum VEGF data. MATERIALS AND METHODS: Dogs surgically treated by partial or complete CPSS attenuation were prospectively recruited. Relative gene expression of VEGF and VEGFR2 was measured in liver biopsy samples taken at initial and follow‐up surgery using quantitative polymerase chain reaction. Serum VEGF concentration was measured before and after CPSS attenuation using a canine specific ELISA. Statistical significance was set at the 5% level (P ≤ .05). RESULTS: There was a significant increase in the mRNA expression of VEGFR2 after partial attenuation (P = .006). Dogs that could tolerate complete attenuation had significantly greater VEGFR2 mRNA expression than those that only tolerated partial attenuation (P = .037). Serum VEGF concentration was significantly increased at 24 (P < .001) and 48 (P = .003) hours after attenuation. CONCLUSIONS AND CLINICAL IMPORTANCE: These findings suggest that intrahepatic angiogenesis is likely to occur after the surgical attenuation of CPSS in dogs, and contributes to the development of the intrahepatic vasculature postoperatively.